Study of pipe thickness loss using a neutron radiography method - Mohamed A.A.; Wahab A.A.B.; Yazid H.B.; Ahmad M.H.A.R.B.M.; Jamro R.B.; Azman A.B.; Zin M.R.M.; Idris F.M. (American Institute of Physics Inc., 2023)
The purpose of this preliminary work is to study for thickness changes in objects using neutron radiography. In doing the project, the technique for the radiography was studied. The experiment was done at NUR-2 facility at TRIGA research reactor in Malaysian Nuclear Agency, Malaysia. Test samples of varying materials were used in this project. The samples were radiographed using direct technique. Radiographic images were recorded using Nitrocellulose film. The films obtained were digitized to processed and analyzed. Digital processing is done on the images using software Isee!. The images were processed to produce better image for analysis. The thickness changes in the image were measured to be compared with real thickness of the objects. From the data collected, percentages difference between measured and real thickness are below than 2%. This is considerably very low variation from original values. Therefore, verifying the neutron radiography technique used in this project. © 2014 AIP Publishing LLC.